A CONTENT ANALYSIS OF STUDENTS’ ENGLISH TEXTBOOK IN CURRICULUM 2013 - Karmila Karmila; Dwi Riyanti; Yohannes Gatot Sutapa Yuliana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2019)
The objective of this research was to analyse the content of students textbook in junior high school at seventh grade based on curriculum 2013. This study aimed to analyse whether the content in the students’ textbook When English Rings the Bell in focus for seventh grade Junior High School are appropriate with the content standard of curriculum K13 or not. In this research, the researcher used document analysis. This document analysis used library research without observing the certain phenomenon directly. The data was taken from the content in the English textbook used in Junior High School at eighth grade students. To collecting the data, the writer used documentary method. For analysing data, the writer presented the content of the English textbook and analyse the content of the English textbook focusing on the grammar aspects. The finding showed that the contents were focussed on certain grammar for junior high school at seventh grade students. The biggest part is Simple Past Tense. It showed that the content of the English textbook for seventh grade Junior High School are appropriate with the content standard of curriculum K13.